(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2017)
The internet security has become the important criteria in the 21st century security applications and its prominence is increasing along with the implementation of the innovative technologies. The data transmission based algorithms has gained popularity in the security domain to provide the protection to the secret information in a reliable way. The secure data transmission is been a concerned area in the field of security and the accidental/incidental attacks on secure data makes it more challenging to provide the ample security without any flaws. The secure image transmission technique paid a lot of attention from the research organizations because of its unique ability to recover the secret image almost losslessly. Although tremendous progress has been made in the past decade on this area but it is consider as unresolved issue in the security domain of the digital image processing domain. The novelty of the proposed method is it automatically transforms the large-volume secret image into a so-called secretfragment- visible mosaic image of the same size. In order to convert the secret image into a mosaic image make use of color transformations is done by dividing the secret image into fragments and transforming their color characteristics to be those of the corresponding blocks of the target image. A scheme namely lossless hiding scheme is utilized along with the key which is used to recover the secret image from the mosaic image by using the information which is embedded into mosaic image. The reliability and efficiency of the proposed method are evaluated by simulation results.